2014
DOI: 10.1016/j.ejmech.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and evaluation of novel heteroaromatic analogs of curcumin as anti-cancer agents

Abstract: To improve the potential of curcumin to treat advanced hormone-refractory prostate cancer, three series (A–C) of heteroaromatic analogs (thirty two compounds) with different monoketone linkers have been synthesized and evaluated for cytotoxicity against two human androgen-independent prostate cancer cell lines (PC-3 and DU-145). Among them, thirty analogs are more potent than curcumin against PC-3 cells, and twenty one analogs are more cytotoxic towards DU-145 cells relative to curcumin. The most potent compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Curcumin was synthesized by Claisen-Schmidt condensation of aromatic aldehyde with acetylacetone according to the procedure described in the literature [31]. 1-Alkyl-1 H -imidazole-2-carbaldehydes ( 36 - 49 ) and 1-alkyl-1 H -benzo[d]imidazole-2-carbaldehydes ( 60 - 65 ) were synthesized according to the procedure described in the literature [12,13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin was synthesized by Claisen-Schmidt condensation of aromatic aldehyde with acetylacetone according to the procedure described in the literature [31]. 1-Alkyl-1 H -imidazole-2-carbaldehydes ( 36 - 49 ) and 1-alkyl-1 H -benzo[d]imidazole-2-carbaldehydes ( 60 - 65 ) were synthesized according to the procedure described in the literature [12,13]. …”
Section: Methodsmentioning
confidence: 99%
“…Extensive research in this field has been conducted by several groups in search for effective curcumin-based anti-cancer agents with favorable safety profiles [10,11]. We have recently identified that (i) 1,5-diheteroarylpenta-1,4-diene-3-ones, exemplified by compounds 2 and 3 in Figure 1, serve as an optimal scaffold for developing potential curcumin-based anticancer agents due to their appreciably enhanced in vitro potency relative to curcumin; and (ii) (1 E ,4 E )-1,5-bis(2-methyl-4-(trifluoromethyl)thiazol-5-yl)penta-1,4-dien-3-one ( 2 ) is a very promising lead compound because of its good in vitro potency and attractive in vivo pharmacokinetic profiles [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…According to the procedure described in the literature, 21 the potassium carbonate-mediated double aldol condensation of the appropriate aromatic aldehyde with acetone was employed to successfully synthesize eleven 1,5-diheteroarylpenta-1,4-dien-3-ones in our previous study. 18 However, most of target compounds for the current study were hard to obtain through the base-catalyzed aldol condensation. After various explorations, we eventually succeeded in synthesizing compounds 6–48 in good yields through the Hornor–Wadsworth–Emmons reaction of 1,3-bis(diethylphosphonato)acetone with the appropriate aromatic aldehyde 22 (Scheme 1).…”
Section: Resultsmentioning
confidence: 98%
“…Encouraged by the potency conferred by the linear dienone linker and the basic aromatic rings, 18 we set out to explore the effect of various heteroaromatic rings on the cytotoxicity of 1,5-diheteroarylpenta-1,4-dien-3-ones against prostate and cervical cancer cell lines. Consequently, forty-three compounds ( 6–48 , Table 1 and Scheme 1) containing two identical terminal five-membered, six-membered, or bulky heteroaromatic rings and a central dienone linker have been designed and synthesized as curcumin mimics for cytotoxic and antiproliferative evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation